2011
DOI: 10.1111/j.1551-6709.2010.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bilateral Motor Behaviors on Flexible Functioning: An Embodied Perspective

Abstract: To examine the influence of bilateral motor behaviors on flexibility performance, two studies were conducted. Previous research has shown that when performing unilateral motor behavior that activates the affective and motivational systems of approach versus avoidance (arm flexion vs. extension), it is the congruence between laterality and motor activation that determines flexibility-rigidity functioning (Cretenet & Dru, 2009). When bilateral motor behaviors were performed, a mechanism of embodiment was reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…This effect has been extended to a task assessing set shifting, the Wisconsin Card Sort Task (Maddox, Filoteo, Glass, & Markman, ). Recent findings on embodied cognition (Cretenet & Dru, ; see also Cretenet & Dru, ) are consistent with the idea that cognitive performance and flexibility could be also influenced through the involvement of multiple motivational and motor activations. Performing a right flexion of the arm; that is, conjointly activating the approach system, or performing a left extension of the arm; that is, conjointly activating the avoidance system, led to an increase in cognitive performance, whereas performing a left flexion of the arm or a right extension of the arm, that is, activating two different systems, led to a decrease in cognitive flexibility.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…This effect has been extended to a task assessing set shifting, the Wisconsin Card Sort Task (Maddox, Filoteo, Glass, & Markman, ). Recent findings on embodied cognition (Cretenet & Dru, ; see also Cretenet & Dru, ) are consistent with the idea that cognitive performance and flexibility could be also influenced through the involvement of multiple motivational and motor activations. Performing a right flexion of the arm; that is, conjointly activating the approach system, or performing a left extension of the arm; that is, conjointly activating the avoidance system, led to an increase in cognitive performance, whereas performing a left flexion of the arm or a right extension of the arm, that is, activating two different systems, led to a decrease in cognitive flexibility.…”
Section: Introductionsupporting
confidence: 64%
“…Another direction of research might be also examined, as the laterality variable would be studied differently from a neuropsychological perspective, referred here (Left and right sides, respectively, as negative and positive for right‐handers). Cretenet and Dru () have recently showed that laterality through motor congruence might correspond either to a neural variable or a psychological one; right‐handers involved also their dominant versus non‐dominant hand when performing a right versus left motor action. Since Casasanto () has recently demonstrated that valence was differently associated with handedness, it would be also important to consider the motor congruence effect on integration information rules, when arm flexion versus extension are performed with the dominant or preferred hand (positive) or the non‐dominant one (negative).…”
Section: Discussionmentioning
confidence: 99%